Uncommon Aggregation‐Induced Emission Molecular Materials with Highly Planar Conformations. Issue 9 (27th February 2018) - Yang, Lei; Ye, Pan; Li, Wenqiang; Zhang, Weijie; Guan, Qian; Ye, Chen; Dong, Tao; Wu, Xiaoxi; Zhao, Weijun; Gu, Xinggui; Peng, Qian; Tang, Benzhong; et al.
Abstract: Numerous luminogenic molecules with twist/rotor structures have showed pronounced aggregation‐induced emission (AIE) effect, while planar conjugated molecules usually exhibit aggregation‐caused quenching (ACQ) characteristics. However, development of emissive organic molecules with planar conformations is beneficial to achieving nanomaterials with high photostability for biological applications. Herein, six analogous planar molecules that show completely contrast emission behavior. 1, 2‐Di(2‐thienyl)‐ethene, 1, 2‐di(2‐selenophenyl)‐ethene, and (E)‐1, 2‐bis(thieno[3, 2‐b]thiophen‐2‐yl)ethene molecules show common ACQ effect, while the planar (E)‐1, 2‐diethyoxy‐1, 2‐di(thiophen‐2‐yl)ethene (TVT(OEt)), (E)‐1, 2‐diethyoxy‐1, 2‐di(selenophen‐2‐yl)ethene (SVS(OEt)), and (E)‐1, 2‐diethyoxy‐1, 2‐di(thieno[3, 2‐b]thiophen‐2‐yl)ethene (TTVTT(OEt)) molecules are highly emissive in the solid state, exhibiting interesting AIE behavior. The experimental and theoretical results demonstrate that the photoisomerization is responsible for the unusual AIE activity of TVT(OEt), SVS(OEt), and TTVTT(OEt). Furthermore, the AIE TTVTT(OEt)‐based nanomaterials exhibit specific imaging of lipid droplets with excellent photostability. The ease with this strategy paves a novel way for creating emissive molecular materials with planar conformations for biological and other applications. Abstract : Introducing ethoxy groups into conjugated systems successfully converts aggregation‐caused quenching molecules to aggregation‐induced emission molecules with planar conformations. (E)‐1, 2‐diethyoxy‐1, 2‐di(thieno[3, 2‐b]thiophen‐2‐yl)ethene based nanomaterials exhibit specific imaging of lipid droplets with excellent photostability. The ease with this strategy paves a novel way for creating emissive molecular materials with planar conformations for biological and other applications.